Sharia Economy As The Foundation Of The People's Economy To Achieve A Prosperous Indonesia - Muarifin; Mohammad Hisyam Yahya; Ahmad Walid (P3M - STAI Kuningan, 2024)
This study examines the role of Islamic economics as the foundation for a people-centered economy in promoting sustainable economic growth and realizing the vision of a prosperous Indonesia. The objective is to analyze how Islamic economic principles grounded in justice, sustainability, and social responsibility can contribute to equitable distribution, community empowerment, and the elimination of harmful economic practices. The research employs a qualitative descriptive method, using literature review and analysis of secondary data from relevant sources on Islamic economic practices and their impacts. The findings reveal that the implementation of Islamic economic instruments such as zakat (almsgiving), waqf (endowments), and Islamic financing plays a significant role in supporting micro, small, and medium enterprises (MSMEs), reducing socio-economic disparities, and strengthening the real sector. These mechanisms contribute to building a more inclusive, stable, and welfare-oriented economic system. In conclusion, Islamic economics holds substantial potential as a foundation for a people-centered economy, offering practical solutions to achieve sustainable development and economic prosperity in Indonesia. This study contributes to the discourse by demonstrating the practical relevance of Islamic economics in addressing contemporary economic challenges and fostering inclusive growth.